The characteristics of Carboniferous volcanic lithofacies and volcanic reservoirs of Ke‐Bai Fault Belt, northwestern Junggar Basin. (14th May 2021) - Yang, Zhi; Zhu, Aiguo; Chen, Yanhui; Yan, Yonghe; Yu, Jingfeng; He, Naixiang; Zhou, Diao; Zhang, Xiaowen; Li, Bin
Abstract : The Ke‐Bai Fault Belt in northwestern Junggar Basin has gained robust insights and wide attention on large‐scale hydrocarbon discoveries in the Carboniferous volcanic rocks. The integrated analysis of wireline logs, image logs, core photographs, thin sections, and scanning electron microscope allows the description and interpretation of volcanic facies and volcanic reservoirs, as well as their responses to controlling factors. The results indicate that three types of lithology are identified based on cores, including volcanic rocks, followed by sedimentary rocks and metamorphic rocks. In addition, explosive facies, effusive facies, volcanic sedimentary facies, and sub‐volcanic facies are delineated according to spatial distribution, occurrence condition, and appearance characteristics of volcanic products. Furthermore, the characteristics of reservoir space (including pores and fractures) are analysed and described. Finally, the controls on the characteristics of volcanic reservoirs are revealed, including volcanic lithofacies, tectonic movements, and diagenesis. Abstract : The significant hydrocarbon reserves resulted from volcanic reservoirs in the cCarboniferous have been discovered in last few decades in Ke‐Bai Fault Belt, northwestern Junggar Basin. Lot of studies have been conducted to identify volcanic lithology and describe reservoir characteristics. However, few of them have been focused on the description and interpretation of volcanic facies and volcanic reservoirs as well as their responses to controlling factors. In this study, the integrated analysis of wireline logs, image logs, core photographs, thin sections, and scanning electron microscope allows the description and interpretation of volcanic facies and volcanic reservoirs as well as their responses to controlling factors. The results indicate that several types of lithology are identified based on cores, including volcanic rocks, followed by sedimentary rocks and metamorphic rocks. In addition, explosive facies, effusive facies, volcanic sedimentary facies, and sub‐volcanic facies are delineated according to spatial distribution, occurrence condition and appearance characteristics of volcanic products. Furthermore, the reservoir space (including pores and fractures) is analysed and characterized. Finally, the controls on volcanic reservoirs are revealed, including volcanic lithofacies, tectonic movements, and diagenesis.